Respuesta :
To rewrite this expression is first you must analyze first the equations and then proceed the the cancellations of values that are the same or having the same variables and the answer for this question is C tan x
Answer with explanation:
The Expression which includes trigonometric functions
⇒(Sec x+Cosec x)(Sin x + Cos x) -2 - Cot x
= (Sec x)×(Sin x) + (Sec x)×(Cos x) + (Cosec x) × (Sin x)+(Cosec x)×(Cos x)-2 -Cot x
= Tan x +1 +1+Tan x +Cot x -2 - Cot x
[tex]\cot x=\frac{\cos x}{\sin x}\\\\ \tan x=\frac{\sin x}{\cos x}[/tex]
= tan x+2+tan x +Cot x -2 - Cot x
→Cancelling Positive and negative like terms
=2 tan x
Option B: 2 tan x